Preparation of Biodiesel from Soybean Oil by using Heterogeneous Catalyst - Khan, Maksudur R.; Ferdous, Kaniz; Uddin, M. Rakib; Islam, M. A. (International Energy and En vironment Foundation, 2013)
The predicted shortage of fossil fuels and related environmental concerns has recently attracted significant attention to search alternative fuel. Biodiesel is one of the alternatives to fossil fuel. Now-adays, most biodiesel is produced by the transesterification of oils using methanol and a homogeneous base catalyst. The use of homogeneous catalysts is normally limited to batch mode processing followed by a catalyst separation step. The immiscible glycerol phase, which accumulates during the course of the reaction, solubilizes the homogeneous base catalyst and therefore, withdraws from the reaction medium. Moreover, other difficulties of using homogeneous base catalysts relate to their sensitivity to free fatty acid (FFA) and water and resulting saponification phenomenon. High energy consumption and costly separation of the catalyst from the reaction mixture have inspired the use of heterogeneous catalyst. The use of heterogeneous catalysts does not lead to the formation of soaps through neutralization of FFA and saponification of oil. In the present paper, biodiesel was prepared from crude (soybean) oil by transesterification reaction using heterogeneous base catalyst name calcium oxide (CaO). Various reaction parameters were optimized and the biodiesel properties were evaluated.